Activity of Ceftazidime–Avibactam Against Respiratory Isolates of Enterobacteriaceae and Pseudomonas aeruginosa Collected in Latin America as Part of the INFORM Global Surveillance Program, 2014–2016. (4th October 2017) - Kazmierczak, Krystyna; Estabrook, Mark; Stone, Gregory G; Sahm, Dan
Abstract: Background: The β-lactam/non-β-lactam β-lactamase inhibitor combination ceftazidime-avibactam (CAZ-AVI) is active in vitro against isolates producing class A, C, and some class D β-lactamases, including extended-spectrum β-lactamases, stably derepressed AmpC, and serine carbapenemases. This study evaluated the in vitro activity of CAZ-AVI and comparators against respiratory isolates of Enterobacteriaceae ( Eba ) and Pseudomonas aeruginosa ( Pae ) collected in Latin America from 2014–2016 as part of the INFORM surveillance program. Methods: Non-duplicate isolates from hospitalized patients with lower respiratory tract infections were collected from 24 medical centers in Argentina, Brazil, Chile, Colombia, Mexico, and Venezuela. Susceptibility (S) testing was performed by broth microdilution and interpreted using CLSI breakpoints except for CAZ-AVI (U.S. FDA) and colistin (EUCAST; Eba only). AVI was tested at a fixed concentration of 4 µg/mL with doubling dilutions of CAZ. Multidrug resistance (MDR) phenotype was defined as resistant by CLSI breakpoints to sentinel agents from ≥3 drug classes. Isolates were screened for β-lactamase genes by PCR and sequencing. Results: CAZ-AVI showed potent in vitro activity against Eba isolates (MIC90, 0.5 µg/mL; 99.3% S) and against CAZ-non-susceptible (CAZ-NS), colistin-resistant (CST-R) and MDR subsets (>93% S). CAZ-AVI activity against meropenem-non-susceptible (MEM-NS) Eba (89.7% S) was reduced due to production of metallo-β-lactamases (MBL); MEM-NS MBL-negative isolates were 100% S. CAZ-AVI showed greater in vitro activity against Pae isolates (MIC90, 32 µg/mL; 85.4% S) than CAZ (69.2% S) or MEM (59.9% S). CAZ-AVI activity against CAZ-NS, CST-R, MEM-NS, MEM-NS MBL-negative, and MDR Pae isolates (50.4–92.6% S) also exceeded that of CAZ and MEM against these resistant subsets. Conclusion: CAZ-AVI is a potential treatment option for respiratory infections in Latin America that are caused by Eba and Pae resistant to commonly used and last-in-line agents. Funding: This study was sponsored by AstraZeneca. The AstraZeneca product ceftazidime-avibactam was acquired by Pfizer in December 2016. Disclosures: G. G. Stone, Pfizer: Employee, Salary AstraZeneca: Shareholder, Capital Gains